Formulasi Pestisida Bentuk Wter Dispersible Granule (WDG) - Emmy Ratnawati (Balai Besar Kimia dan Kemasan, 1997)
Water Dispersible Granule (WDG) as a modification of Wettable Powder and Granule formulation is the new type of pesticide formulation in the form of granule. Like Wettable Powder, the aplication of this formulation is by dispersing it in water. WDG is consist of active ingredient, carrier, wetting agent, dispersing agent, and binding agent. According to those compositions WDG must have the properties such as very good dispersibility in water, no breaking and dusting during handling, high active content and have physical and chemical stability. Base on the type of active ingredient, WDG can be produced through two processes of preparation step i.e. wet process and dry process followed by granulation step which can be done by spray dryer, pan granulator, fluid bed, extrusion and high speed mixer.